Blended Learning: The Effect on Higher Order Thinking Skills (HOTS) in Thermodynamics - Saefullah, Asep; Fitriyani, Amalia; Ruhiyat, Yayat; Rostikawati, Diana Ayu (Indonesian Journal of Science and Mathematics Education, 2020)
This study aims to determine the effect of the application of the blended learning model to improving higher order thinking skills (HOTS) on thermodynamic material. The research method used in this study is quasi-experimental, while the research design used is Non Equivalent Design. Samples were taken using purposive sampling technique, with class XI MIA 1 as an experimental class and XI MIA 2 as a control class. The instrument used in this study was an HOTS test item in the form of multiple choice questions. Data analysis techniques using SPSS software to test hypotheses, and Microsoft Excel to determine the magnitude of the increase in HOTS. The results of the independent sample t-test showed a significance value (2-tailed) of 0.03. Large increase in the experimental class by 0.50 (50%), and by 0.40 (40%) in the control class. This shows that learning using the blended learning model has a better effect in HOTS than learning without blended learning.